2017
DOI: 10.1111/jar.12308
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Economic Well‐Being of US Mothers with Intellectual Impairments

Abstract: Findings from this study indicate the need for policies and programmes to support parents with intellectual impairments by addressing their health and economic needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…This includes not only working with them to modify their health behaviors to decrease perinatal risk but also supporting them more broadly in recognition that women with disabilities are marginalized in many ways (eg, low socioeconomic status, little social support, high rates of abuse, experiences of stigma and discrimination). 10,12,70,87 During the perinatal period, some women with disabilities may require close monitoring by their health care providers through more frequent and longer visits as well as specialized care. In addition to the perinatal complications examined herein, issues that are common in pregnancy such as fatigue, fluid retention, and urinary tract infections can be more pronounced in some women with disabilites, 67,71,81,84,88 and pregnancy may also have an impact on the course of the disability.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…This includes not only working with them to modify their health behaviors to decrease perinatal risk but also supporting them more broadly in recognition that women with disabilities are marginalized in many ways (eg, low socioeconomic status, little social support, high rates of abuse, experiences of stigma and discrimination). 10,12,70,87 During the perinatal period, some women with disabilities may require close monitoring by their health care providers through more frequent and longer visits as well as specialized care. In addition to the perinatal complications examined herein, issues that are common in pregnancy such as fatigue, fluid retention, and urinary tract infections can be more pronounced in some women with disabilites, 67,71,81,84,88 and pregnancy may also have an impact on the course of the disability.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Moreover, research has demonstrated high levels of contextual risk factors for caregiving and child developmental problems in the lives of families headed by parents with ID (Feldman & Aunos, 2020). For instance, parents with ID are often socioeconomically disadvantaged (Powell et al, 2017), and struggle with mental health problems (O’Keeffe & O’Hara, 2008), social isolation (Llewellyn & Hindmarsh, 2015), and parenting stress (Meppelder et al, 2015). Such risk factors are strongly linked to caregiving difficulties and negative child outcomes in the general population (e.g., Neppl et al, 2016; Plass-Christl et al, 2017; Stith et al, 2009).…”
mentioning
confidence: 99%
“…In this special issue, Lindberg, Fransson, Forslund, Springer, and Granqvist report substantial variation in the sensitivity of Swedish mothers with intellectual disabilities associated with the quality of care received or exposure to maltreatment in their own upbringing. The paper by Powell and Parish also highlights contextual factors. Analysing big data in the USA, they find that mothers with intellectual impairments are more likely to live in poverty, report serious health issues and have less instrumental support than mothers without intellectual impairments.…”
Section: Contextual Factorsmentioning
confidence: 98%